The Humanistic Education Model in Virtual Learning During COVID 19 Pandemic - Firman Mansir (JSPH (Jurnal Sosiologi Pendidikan Humanis), 2022)
Humanistic education conceptually can build peace of mind and body to achieve the virtues of a learner's life. The perfection of this life can be directed to the development of personality that includes thinking, mental strength and creativity of students by developing patterns of individual human development. The results of this study indicate that the concept of humanization and the nature of education is the element that can best distinguish humans by using their thoughts because this is a gift of reason that has been given by the creator. In addition, humans are free to use it through the learning process. This research used a qualitative approach and literature analysis as a method of data analysis. Thus, to respond to virtual learning during the COVID-19 pandemic, it is necessary to prioritize and apply education and methods that are better able to understand the human condition as learners. It is expected that through this process, general educational goals can be achieved and specific learning objectives can be realized.